The Effect of LED Light Intensity on the Growth of Spinach (Amaranthus sp.): A Comparative Study of Green and Red Varieties - Intharit, Supamas; Navarro, Leah; Chanudom , Apichai (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to examine the effect of LED light power on the growth of spinach plants (Amaranthus sp.) and compare the impact of different LED power levels on the growth of green and red spinach. Methodology: This study used white LED lights (3W, 5W, 6.5W), a lux meter, thermometer, ruler, and camera. Green and red spinach seeds were planted in polybags with a soil and fertilizer mixture. An experimental method was applied with weekly growth measurements. Data were analyzed using descriptive statistical calculations. Main Findings: The results show that 3W LED light provides the best growth for green and red spinach, with greater leaf width, leaf count, and stem height compared to 5W, 6.5W, and no light. Excess light (6.5W) hinders growth, while no light causes pale and wilted leaves. Red spinach grows faster than green spinach. Novelty/Originality of this study: This study reveals that 3W LED light is more effective in promoting spinach growth than higher wattages or no additional light. These findings provide new insights into optimal light power selection for plant growth, benefiting urban farming, hydroponics, and indoor cultivation.